Organizational Strategy Analysis to Increase Competitiveness Using SWOT and QSPM Methods at U.D. Garuda Jaya - Ayu Prema Laksmi; Rizqa Amelia Zunaidi (University of Merdeka Malang, 2023)
U.D. Garuda Jaya is a furniture industry located in Bajera Village, Tabanan Regency, Bali Province. In running its business, U.D. Garuda Jaya found problems such as product sales that did not increase and decreased competitiveness. The methods used are the Porter matrix, SWOT, and QSPM. Data in the study were obtained from interviews based on the 7P marketing mix. The results of the first order of alternative strategic priorities are to develop a good organizational structure so that each process in the company can run according to its respective tasks to maximize its productivity and make U.D. Garuda Jaya is the only furniture SME in Bajera Village with a TAS value of 5.082. The second alternative strategy is to increase employee creativity in designing U.D. Garuda Jaya’s distinctive products in order to improve product quality and competitiveness with new competitors have emerged with a TAS value of 4.836. The third strategy is to recruit employees who are competent in their fields and provide training to employees by utilizing technological advances to be able to produce distinctive product designs from U.D. Garuda Jaya with a TAS value of 4.819.